DENGUE HEMORRHAGIC FEVER INCLINATION TENDENCY IN EAST JAVA PROVINCE VILLAGES COMMUNITY-BASED TOTAL SANITATION: Kecenderungan Kejadian Demam Berdarah Dengue Menurut Cakupan Desa Sanitasi Total Berbasis Masyarakat di Jawa Timur - Griseld Adiel Farahita; Lucia Yovia Hendrati; Geofrey Ssekalembe (Jurnal Berkala Epidemiologi, 2023)
Background: Dengue Hemorrhagic Fever (DHF) is one of the endemic diseases throughout the tropics and parts of the subtropics. One of the provinces that felt the impact of the dengue outbreak was East Java. Overall, villages implementing STBM coverage in East Java Province is good but incidence of DHF is still found in all districts or cities in the last 3-year period. Purpose: This study aims to analyze the relationship and the inclination tendency of Dengue Hemorrhagic Fever in East Java). Methods: This type of research is an observational study with a cross-sectional study design. The sample population used 38 regencies/cities in East Java Province. The data used are the health profile data of East Java Province in 2018, 2019, and 2020. The data analysis technique used descriptive by utilizing the Health Mapper application version 4.3.0.0 with product version 4.03. Results: The distribution of DHF incidence with the coverage of villages implementing STBM East Java in 2018, 2019, 2020 showed decrease the coverage of villages implementing STBM is also followed by an increase DHF cases every year. The coverage of villages that implement Community Based Total Sanitation (STBM) fluctuates every year. Conclusion: Areas with STBM villages cannot guarantee DHF-free zones but can prevent the transmission of Dengue Hemorrhagic Fever (DHF) by changing hygiene and sanitation behavior through community empowerment to create a good sanitation.